On Distance Function in Some New Analytic Bergman Type Spaces in ℂn - Romi F. Shamoyan; Olivera R. Mihić (Journal of Function Spaces)
We extend our previous sharp results on distances obtained for analytic Bergman type spaces in unit disk to some new analytic Bergman type spaces in higher dimensions in ℂn. Also, we study the same problem in anisotropic mixed norm h(p,q,s) spaces consisting of n-harmonic functions on the unit polydisc of ℂn.